The impact of donor-recipient age difference on graft survival after heart transplant in adults with congenital heart disease - William H. Marshall, V, MD; Brent C. Lampert, DO; Curt J. Daniels, MD; Deipanjan Nandi, MD; Lydia K. Wright, MD (JHLT Open)
Background: The impact of donor-recipient age difference in adult congenital heart disease (ACHD) patients undergoing heart transplant (HT) is unknown. Methods: ACHD patients (≥18 years old) who underwent HT (2000-2020) were identified using the United Network for Organ Sharing database. Graft survival through 10 years based on donor-recipient age difference was evaluated by comparing outcomes of donors >5 years older than recipients (Older), donors within 5 years of recipient age (Equal Age), and donors >5 years younger than recipients (Younger, reference group). Cox multivariable analysis was performed to evaluate the effect of donor-recipient age difference on early and late graft survival. Results: A total of 1,275 ACHD patients underwent HT (60% male, median 35 years old (interquartile range 24-46) with median graft survival of 13.7 years (95% confidence interval [CI] 11.7-16.0). Compared to Younger donors (n = 306 [24%]), graft survival was similar with Equal Age donors (n = 698 [55%]; log-rank p = 0.61), though significantly reduced with Older donors (n = 271 [21%]; log-rank p = 0.03). In multivariable analysis, late graft survival was similar with Equal Age donors but lower with Older donors (adjusted hazard ratio 1.63, 95% CI 1.16-2.28, p = 0.005), with a trend of reduced survival with Older donors in recipients <30 or ≥40 years old. Conclusions: Graft survival in ACHD patients undergoing HT was similar for those with Younger and Equal Age donors. Recipients with Older donors had reduced 10-year survival, possibly related to increased risk in those <30 and ≥40 years old. These data help inform the optimal donor age for ACHD patients requiring HT.